Fabrication of P-MoO2-Fe3O4 nanobelts for efficient overall water splitting. (15th January 2023) - Cui, Zhijie; Feng, Tiantian; Wang, Xuehong; Guo, Pengfei; Wang, Wenpin; Yue, Mei-E; Li, Zhongcheng
Graphical abstract: Shape- and size-controlled P-MoO2 -Fe3 O4 nanobelts with the interface structures and defective sites are fabricated, which is highly active in water oxidation and water dissociation. Highlights: Shape and size control of P-MoO2 -Fe3 O4 nanobelts are prepared. Interface structures and defective sites are identified on P-MoO2 -Fe3 O4 . The unique nanostructures contribute to promoting water electrolysis. Abstract: Recent studies indicate that irregular MoO2 nanomaterials are much less active in oxygen evolution reaction and water electrolysis due to poor electron transfer. The catalytic performance for MoO2 is essential to be mediated by tailoring its shape, size, and composition. Here, we develop a simple approach to realize shape and size control of P-MoO2 -Fe3 O4 nanobelts with 150–230 nm in diameter, inheriting from α-MoO3 nanobelts. Surface structure analysis reveals doping of P into MoO2 -Fe3 O4, generation of interfacial structure between MoO2 -Fe3 O4, and defective structures. At 10 mA/cm 2, P-MoO2 -Fe3 O4 nanobelts achieve superior oxygen evolution reactivity with 270 mV to RuO2 with 319 mV and exhibit higher hydrogen generation activity (200 mV) compared with P-MoO2 nanobelts (250 mV) and P-Fe3 O4 nanosheets (220 mV). The unique structures with interface of MoO2 -Fe3 O4 and defective sites for P-MoO2 -Fe3 O4 nanobelts promote overall water splitting reactivity.